Use of Neonatal Lung Ultrasound for the Early Detection of Pneumothorax - Deng, Bi-Ying; Li, Ning; Wu, Wen-Shen; He, Xiao-Guang; Li, Jin-Feng; Huang, Tian-li; Li, Yu-Chan; Jiang, Shuang-lan (American Journal of Perinatology, 2020)
Objective Pneumothorax (PTX) can be diagnosed using lung ultrasonography (LUS) in adult patients, but there are only a few reports of LUS in PTX diagnosis in neonates. The aim of the study was to assess the diagnostic accuracy for PTX.Study Design This was a retrospective review study performed in our neonatal intensive care unit (level III) between June 2015 and June 2018. All eligible patients underwent an LUS scan before undergoing a chest X-ray (CXR), which was considered the reference standard. When a diagnosis of PTX was inconsistent between LUS and CXR, a chest computed tomography (CT) scan or chest drain was considered the gold standard.Results Among 86 infants included in the study, 30 (34.9%) were diagnosed with PTX. In these 30 infants, 35 PTXs were detected by bedside LUS (five bilateral PTXs). Moreover, 11 infants with 14 PTXs were diagnosed only by LUS and were missed by CXR. Out of these 11 infants, 7 underwent a CT scan, whereas the remaining 4 underwent thoracentesis that confirmed PTX diagnosis.Conclusion In neonates with PTX, LUS was more sensitive and specific for the early detection of PTX compared with CXR.
Keywords: pneumothorax; lung ultrasonography; neonate; diagnosis